Comparison of Long Term Anti-Tnf Survival in Patients with Ankylosing Spondylitis and Non-Radiographic Axial Spondyloarthritis; Data from Turkbio Registry - Can, Gercek; Dalkilic, Ediz; Pehlivan, Yavuz; Senel, Soner; Akar, Servet; Solmaz, Dilek; Onen, Fatos (Wiley, 2017)
[Abstract Not Available]
81st Annual Meeting of the American-College-of-Rheumatology (ACR) / Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 03-08, 2017 -- San Diego, CA